The INFLUENCE OF LOCATION AND CAFE ATMOSPHERE ON CONSUMER SATISFACTION IN BELI KOPI SIDOARJO: PENGARUH LOKASI DAN CAFE ATMOSPHERE TERHADAP CONSUMER SATISFACTION DI BELI KOPI SIDOARJO - Suprehatin Siti Romelah; Muhammad Arif Wicaksono; Nazila Wiji Rochmah (TALI JAGAD JOURNAL, 2023)
The purpose of this study was to determine the effect of location and café atmosphere on Consumer Satisfaction at Belikopi Sidoarjo, right on Jl. Untung Surapati No. 11, Sidokumpul, Sidoarjo. The population in this study were Belikopi consumers who were 100 respondents using a Likert scale. The methodology used in this research is to use descriptive quantitative metode. Determination of the sample in this study using accidental sampling, namely anyone who happens or incidentally meets the researcher can be used as a sample. The results of this study indicate that the location variable partially has a negative effect on consumer satisfaction, while the café atmosphere variable partially has a positive effect on consumer satisfaction. But simultaneously the location and café atmosphere variables positively affect consumer satisfaction.